The effectiveness of hedging between Crude Palm Kernel Oil (CPKO) spot price and Futures Crude Palm Oil Contract (FCPO) in Malaysia - Tham, Poh Seng (2024)
The Malaysian palm oil market, a crucial component of the global edible oils industry, experiences significant price volatility, particularly in crude palm kernel oil (CPKO). This volatility presents substantial challenges for market participants in managing financial risks. This study examines the relationship between CPO's futures price and the hedging effectiveness of CPKO's spot price. It also investigates the relationship between unhedged and hedged portfolios and assesses the hedging effectiveness of FCPO contracts in mitigating CPKO price volatility. Advanced econometric techniques, including regression analysis, GARCH models, and time series analysis, were applied to a comprehensive dataset of daily CPKO spot prices and FCPO contracts from January 2010 to June 2022. This 12-year period provides a detailed examination of long-term market dynamics and price fluctuations in the Malaysian palm oil industry. The findings indicate a significant positive impact between FCPO and CPKO prices using the Naive 1-to-1 approach. The GARCH 1:1 model demonstrates enhanced risk reduction through time-adjusted hedge ratios. However, the Optimal Hedge Ratio (OHR) calculation reveals the complexities of using FCPO futures for hedging CPKO, as evidenced by a negative OHR. These results contribute significantly to hedging theory, particularly in emerging markets, by validating the application of regression and time series models in understanding the dynamics between spot and futures prices within the palm oil industry. Traders, producers, and policymakers for Crude palm kernel oil should emphasize the need for adaptable and effective hedging strategies to manage price risks within the palm oil industry. FCPO contracts may help stabilize price fluctuations, offering stability and predictability for the palm oil industry. Continuous adaptation and refinement of hedging strategies are essential for effectively mitigating risks